Comparing the effect of plasma therapy with estradiol valerate in motor and cognitive behavioral disorders in ovariectomized old rats: Behavioral, biochemical, and protein expression - Maryam Khajvand-Abedini; Mohammad Mohammadi; Parisa Habibi; Zahra Shahabi‬; Siamak Shahidi; Naser Ahmadiasl; Mohammad Reza Alipour; Mahdi Ramezani; Alireza Komaki (Iranian Journal of Basic Medical Sciences)
Objective(s): This study investigated the effects of young plasma therapy (YPT) compared to estrogen therapy (E2T) on motor and cognitive impairments in aged ovariectomized (OVX) rats.Materials and Methods: Sixty female Wistar rats were divided as follows: 1). 2-3 months control young group. Five 22-24 months old groups: 1) Control, 2) Sham, 3) OVX, 4) OVX.E2, and 5) OVX.YP. Young plasma (1 ml plasma, through the tail vein, 3 days weekly for 4 weeks) and E2 (30 mg/kg, SC, 5 days weekly for 4 weeks) were administrated to OVX rats. The open field, elevated plus maze, and Barne’s maze were used to assess the behaviors. Then, miR-134 and miR-124 (RT- RCR), SIRT1, CREB, and BDNF (western blot), and anti-oxidants/oxidants markers (Photometry) levels were assessed in the rat’s hippocampal tissues.Results: OVX caused up-regulated hippocampal miR-134 and miR-124 expression levels (P<0.001) while down-regulated SIRT1, CREB, and BDNF protein expressions (P<0.001). Also, ovariectomy Increased TOS, OSI, and MDA (P<0.001) while decreasing TAC (P<0.001) compared to sham. Treatment with both E2T and YPT significantly improved all oxidative stress indexes (P<0.0.001) and increased p-CREB, BDNF, and SIRT1 protein levels (P<0.05, P<0.01) while decreasing the expression of miR-134 and miR-124 (P<0.001). Conclusion: YPT is a non-pharmacological therapeutic as much as or more than E-2T, which can exhibit anti-oxidative and anti-inflammatory potential in the hippocampal tissue and improve cognitive deficits in aged OVX rats without unknown side effects.